Critical Thinking and Ideology in Chinese Higher Education - Du, Xiaoxin (International Higher Education, 2019)
This article takes Fudan University in Shanghai, China, as an example to show the complex interaction among players in the process of socialization through political education and academic affairs. The roles of teachers have been split between enforcing political socialization and pursuing academic freedom—alternating between obediently observing political bottom lines and attempting to expand the scope of their academic autonomy.